Two‐Year observational study of autonomic skin function in patients with Parkinson's disease compared to healthy individuals. (24th February 2023) - Siepmann, Timo; Arndt, Martin; Sedghi, Annahita; Szatmári, Szabolcs; Horváth, Tamás; Takáts, Annamária; Bereczki, Dániel; Moskopp, Mats Leif; Buchmann, Sylvia; Skowronek, Cornelia; Zago, Wagner; Woranush, Warunya; et al.
Abstract: Background and purpose: We characterized autonomic pilomotor and sudomotor skin function in early Parkinson's disease (PD) longitudinally. Methods: We enrolled PD patients (Hoehn and Yahr 1–2) and healthy controls from movement disorder centers in Germany, Hungary, and the United States. We evaluated axon‐reflex responses in adrenergic sympathetic pilomotor nerves and in cholinergic sudomotor nerves and assessed sympathetic skin response (SSR), predominantly parasympathetic neurocardiac function via heart rate variability, and disease‐related symptoms at baseline, after 2 weeks, and after 1 and 2 years. Clinicaltrials.gov : NCT03043768. Results: We included 38 participants: 26 PD (60% females, aged 62.4 ± 7.4 years, mean ± SD) and 12 controls (75% females, aged 59.5 ± 5.8 years). Pilomotor function was reduced in PD compared to controls at baseline when quantified via spatial axon‐reflex spread (78 [43–143], median [interquartile range] mm 2 vs. 175 [68–200] mm 2, p  = 0.01) or erect hair follicle count in the axon‐reflex region (8 [6–10] vs. 11 [6–16], p  = 0.008) and showed reliability absent any changes from baseline to Week 2 ( p  = not significant [ns]). Between‐group differences increased over the course of 2 years ( p  < 0.05), although no decline was observed within groups ( p  = ns). Pilomotor impairment in PD correlated with motor symptoms (rho = −0.59, p  = 0.017) and was not lateralized ( p  = ns). Sudomotor axon‐reflex and neurocardiac function did not differ between groups ( p  = ns), but SSR was reduced in PD ( p  = 0.0001). Conclusions: Impairment of adrenergic sympathetic pilomotor function and SSR in evolving PD is not paralleled by changes to cholinergic sudomotor function and parasympathetic neurocardiac function, suggesting a sympathetic pathophysiology. A pilomotor axon‐reflex test might be useful to monitor PD‐related pathology. Abstract : Our observational study demonstrated impaired adrenergic sympathetic pilomotor function and reduced sympathetic skin response in patients with Parkinson's disease (PD) compared to healthy individuals with increasing between‐group differences over the course of 2 years. Sympathetic adrenergic changes were not paralleled by changes to cholinergic sudomotor function and parasympathetic neurocardiac function, suggesting a sympathetic pathophysiological mechanism. A pilomotor axon‐reflex test might be a useful tool to monitor PD‐related pathology.